2017
DOI: 10.1590/0104-6632.20170341s20150231
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the Long-Term Stability and Kinetics of Superoxide Ion in Dimethyl Sulfoxide Containing Ionic Liquids and the Application of Thiophene Destruction

Abstract: -after the introduction of the IL was monitored using a UV-vis spectrophotometer. The ammoniumbased ILs were found to be more stable than piperidinium-based ILs. To the best of our knowledge, this was the first time that O2 − stability with ILs has been monitored continuously for up to 24 h. This should provide a better insight into the stability and kinetics of O2 − for industrial applications and its role in energy-storage devices. The most appropriate IL as a medium was [EDMPAmm][TFSI], and O2 − generate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 72 publications
0
3
0
Order By: Relevance
“…In general, this implied that the reduction of O 2 commences in the bulk phase of the IL; as a result, there is no reduction of O 2 at the surface of the GC electrode. Also, this observation strongly suggested that the electrochemical process was kinetically rapid, and in the presence of reversed oxidation CV waves, the O 2 · – generated was stable in [EDMPAmm + ]­[TFSI – ], [MOEMMor + ]­[TFSI – ], and [PMIm + ]­[TFSI – ] . By comparing Figure a–c and Figure S1a–c, a contacting pattern of CO 2 and O 2 in the IL becomes immaterial; hence, the two figures show similar CV waves for O 2 reduction.…”
Section: Resultsmentioning
confidence: 78%
See 2 more Smart Citations
“…In general, this implied that the reduction of O 2 commences in the bulk phase of the IL; as a result, there is no reduction of O 2 at the surface of the GC electrode. Also, this observation strongly suggested that the electrochemical process was kinetically rapid, and in the presence of reversed oxidation CV waves, the O 2 · – generated was stable in [EDMPAmm + ]­[TFSI – ], [MOEMMor + ]­[TFSI – ], and [PMIm + ]­[TFSI – ] . By comparing Figure a–c and Figure S1a–c, a contacting pattern of CO 2 and O 2 in the IL becomes immaterial; hence, the two figures show similar CV waves for O 2 reduction.…”
Section: Resultsmentioning
confidence: 78%
“…•− in our previous studies. 14,[18][19][20]38,41,57 In addition, ultrahigh pure N 2 (99.999%), CO 2 (99.999%), and O 2 (99.999%) were purchased from Gaslink SDN Malaysia.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation